Urban Forestry - Tewari, D. N. (Indian Forester, 1994)
As a concept, urban forestry is a relatively new one, both for foresters and for the general public. There is a consensus in the view that quality of urban life depends largely on the amount and quality of green spaces within it or close to it. The increase of urban dwellers is responsible for reduction in green space and treeless areas. Urbanisation near sea coasts deserts and on the banks of important rivers is responsible for environmental degradation and biodiversity erosion. Urban forestry can improve the environment for better living and conserve biodiversity of mangrove and other fragile ecosystems in and around cities.